2021
DOI: 10.1097/jcma.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

Image-enhanced endoscopy for detection of second primary esophageal neoplasms in patients with hypopharyngeal cancer: Prevalence, risk factors, and characteristics

Abstract: Background: Esophageal second primary neoplasms (ESPNs) are common in hypopharyngeal squamous cell carcinoma (HPSCC) patients and are associated with poor prognoses. The effectiveness of image-enhanced endoscopy (IEE) has not been well established. Methods: We reviewed the patients between April 2016 and April 2018 with HPSCC receiving ESPNs screening via white-light imaging, narrow-band imaging, and Lugol chromoendoscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Similar to patients with Barrett’s esophagus prone to developing EIN and EC during their lives, 5 in the current study, the authors found that patients with past or newly-diagnosed HPSCC had a higher risk of synchronous EIN/EC or subsequent development of EIN/EC. 9 As shown in the current study, 9 more than one-fourth of the newly-diagnosed HPSCC patients have a synchronous EIN/EC (10% for invasive EC and 16.7% for EIN). 9 It is very important that all patients with a newly-diagnosed HPSCC should undergo the detailed and thorough evaluation of the upper aerodigestive tract and lung, because of high incidence or high prevalence (>25%) of synchronous or metachronous SCC in oral cancer patients based on the current study.…”
supporting
confidence: 54%
See 4 more Smart Citations
“…Similar to patients with Barrett’s esophagus prone to developing EIN and EC during their lives, 5 in the current study, the authors found that patients with past or newly-diagnosed HPSCC had a higher risk of synchronous EIN/EC or subsequent development of EIN/EC. 9 As shown in the current study, 9 more than one-fourth of the newly-diagnosed HPSCC patients have a synchronous EIN/EC (10% for invasive EC and 16.7% for EIN). 9 It is very important that all patients with a newly-diagnosed HPSCC should undergo the detailed and thorough evaluation of the upper aerodigestive tract and lung, because of high incidence or high prevalence (>25%) of synchronous or metachronous SCC in oral cancer patients based on the current study.…”
supporting
confidence: 54%
“…9 As shown in the current study, 9 more than one-fourth of the newly-diagnosed HPSCC patients have a synchronous EIN/EC (10% for invasive EC and 16.7% for EIN). 9 It is very important that all patients with a newly-diagnosed HPSCC should undergo the detailed and thorough evaluation of the upper aerodigestive tract and lung, because of high incidence or high prevalence (>25%) of synchronous or metachronous SCC in oral cancer patients based on the current study. 9 In fact, surveillance programs of the upper aerodigestive tract and lung cancers are mandatory to detect synchronous or metachronous SCC, including EC at early stages.…”
supporting
confidence: 54%
See 3 more Smart Citations